Efeito do Programa Alimentar Brasileiro Cardioprotetor sobre os componentes do risco cardiometabólico em pacientes cardiovasculares - Rocha, Bárbara Rafaela Santos da (2016)
Cardiovascular disease is the leading cause of death in the world, in Brazil it is main manifestation is coronary artery disease. The lifestyle and dietary pattern seem to be the main determinants of the manifestation of cardiometabolic risk factors for cardiovascular disease and diabetes. Given this situation, the aim of this study was to evaluate the effect of the Programa Alimentar Brasileiro Cardioprotetor (Brazilian Cardioprotective Nutritional Program) in food intake and cardiometabolic risk components, abdominal obesity, hyperglycemia, hypertension, hypertriglyceridemia and reduced serum high-density lipoprotein. This was a randomized, dietary intervention trial, based on reducing nutrient density favorable to cardiovascular diseases: calories, saturated fat, sodium and cholesterol. Control group (n=31) and intervention group (n=27) were homogeneous in relation to sociodemographic, clinical, anthropometric and biochemical characteristics. Intervention group with a nutritionist follow up reduced consumption of calories, total fat, saturated fat, trans fat and sodium. The control group with food guidance to nurses and pharmacists no change in food intake. The effect of the nutritional program on cardiometabolic risk after the intervention was observed in reducing fasting glucose levels by comparing the intervention and control groups. The other parameters of cardiometabolic risk were not statistically significant. Hyperglycemia reduction in the intervention group using a multivariate analysis adjusted for use of hypoglycemic drug, gender and age was 40% by decreasing abdominal obesity in 3,90cm (r² = 0.474, β = 0.654, p = 0.007), weight and BMI also explained the reduction in serum glucose by 17% and 0.07%, respectively. The Brazilian Nutritional Programme effect was in reducing the consumption of lipids and sodium, with metabolic consequences in the reduction of hyperglycemia and evolution of anthropometric parameters. Indicating that improving the diet in chronic patients is a slow process because it involves changes in lifestyle.